2020
DOI: 10.31234/osf.io/j5n28
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CogEpiCrim - The M-Theory of Suicidology

Abstract: For the past century, suicide has been associated with negative connotations to the liberalistic connotations, however, the fabric of logic and reason behind suicidal ideation continues to exist with countless wrinkles and folds. In my manuscript, a new approach to address the age-old question is provided – CogEpiCrim, which extends the boundaries of our understanding by using the suicidal ideation, not the action, as an infectious disease that can spread across closed communities. The paper describes how CogE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The surface area of the bond, and these changes in the functional groups of the bioactive molecules indicate that they are related to the formation of the Cu/Cs-NPs nanocomposite. These results are consistent with [12] who reported that the chemical groups were transformed, which indicates that the successful loading of the methanolic extract of pumpkin plant peels on Chitosan compound, and its association with TPP compound, which leads to the formation of the Cu/Cs-NPs nanocomposite. There was other supporting evidence for the formation of the nanocomplex published by [38] who reported that the changing peaks indicated the formation of a new compound.…”
Section: Fourier Transformation Infrared Spectroscopy (Ftir)supporting
confidence: 91%
See 2 more Smart Citations
“…The surface area of the bond, and these changes in the functional groups of the bioactive molecules indicate that they are related to the formation of the Cu/Cs-NPs nanocomposite. These results are consistent with [12] who reported that the chemical groups were transformed, which indicates that the successful loading of the methanolic extract of pumpkin plant peels on Chitosan compound, and its association with TPP compound, which leads to the formation of the Cu/Cs-NPs nanocomposite. There was other supporting evidence for the formation of the nanocomplex published by [38] who reported that the changing peaks indicated the formation of a new compound.…”
Section: Fourier Transformation Infrared Spectroscopy (Ftir)supporting
confidence: 91%
“…Deionized or ion-free distilled water was used as a control or comparison element. Absorbance was taken at a wavelength (200 -800 nm), and the concentrated samples were diluted at 10:1 in deionized water [12].…”
Section: Spectroscopy Absorption Visible-uvmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 outlines the most common rigid polymers used in microfluidics and a few of their general properties. [46][47][48][49] For more extensive information please see reviews by Gencturk et al 50 and Tsao. 51 Polymethyl methacrylate (PMMA) is widely used in research laboratories because it is optically transparent and can be manipulated with fabrication methods such as hot embossing, laser ablation, or precision milling.…”
Section: Rigid Polymersmentioning
confidence: 99%